Unequal Working Futures and Machine Intelligence - Sangarapillai, Vahini (2023)
Sonya, a participant in this study, talking about technological change, said it is important to ‘imagine, remember before.’ From remembering to imagining, I explore workers’ imagined working futures as influenced by social positions, drawing on Bourdieu’s concepts of capitals and habitus, which offers a relational view of the future of work.